Photo‐Induced C(sp3)−H Functionalization for the Synthesis of 3, 3‐Disubstituted Oxindoles. Issue 5 (26th April 2022) - Xu, Dongping; Yu, Yingliang; Huang, Fei; Zhou, Shuangliu; Zhang, Wu
Abstract: An efficient photo‐induced direct oxidative radical cascade cyclization of N ‐arylacrylamides with aliphatic alcohols at ambient temperature was developed. The present reaction exhibits a wide substrate scope, and various valuable oxindoles can be effectively accessed through the direct sp 3 C−H functionalization of alcohols, ethers, cyclohexane, toluene and acetonitrile. Importantly, this cascade reaction proceeds photocatalyst‐free, at room temperature, utilizes readily available starting materials, and has a broad substrate scope. Abstract : An efficient photo‐induced oxidative radical cascade cyclization of N ‐arylacrylamides with various Csp 3 −H coupling components at ambient temperature for the synthesis of 3, 3‐disubstituted oxindoles was developed.